Automated Reasoning Third International Joint Conference, IJCAR 2006, Seattle, WA, USA, August 17-20, 2006, Proceedings - Furbach, Ulrich; Shankar, Natarajan (Lecture Notes in Artificial Intelligence, 2006)
This book constitutes the refereed proceedings of the Third International Joint Conference on Automated Reasoning, IJCAR 2006, held in Seattle, WA, USA in August 2006 as part of the 4th Federated Logic Conference, FLoC 2006. IJCAR 2006 is a merger of CADE, FroCoS, FTP, TABLEAUX, and TPHOLs. The 41 revised full research papers and 8 revised system descriptions presented together with 3 invited papers and a summary of a systems competition were carefully reviewed and selected from a total of 152 submissions. The papers address the entire spectrum of research in automated reasoning including formalization of mathematics, proof theory, proof search, description logics, interactive proof checking, higher-order logic, combination methods, satisfiability procedures, and rewriting. The papers are organized in topical sections on proofs, search, higher-order logic, proof theory, search, proof checking, combination, decision procedures, CASC-J3, rewriting, and description logic.